Solute carrier family 2 member 2 (glucose transporter 2): a common factor of hepatocyte and hepatocellular carcinoma differentiation - Yejin Kim; Yu Yeuni; Hye Jin Heo; Eun Sun Kim; Kyungjae Myung; Ninib Baryawno; Yun Hak Kim; Chang-Kyu Oh (PLoS ONE, 2025)
GLUT2 (SLC2A2), a vital glucose transporter in liver, pancreas, and kidney tissues, regulates blood glucose levels and energy metabolism. Beyond its metabolic role, SLC2A2 contributes to cell differentiation and metabolic adaptation during embryogenesis and tissue regeneration. Despite its significance, the role of SLC2A2 in liver differentiation and hepatocellular carcinoma (HCC) remains underexplored. This study investigated SLC2A2’s role in liver differentiation using in silico, in vitro, and in vivo approaches. Analysis of GEO datasets (GSE132606, GSE25417, GSE67848) and TCGA HCC data revealed that while SLC2A2 expression decreases with HCC progression, stemness-associated genes, including SOX2 and POU5F1, are upregulated. Zebrafish embryos injected with SLC2A2-targeting morpholino exhibited reduced expression of the liver differentiation marker fabp10a without significantly altering the hepatoblast marker hhex. In HepG2 cells, SLC2A2 knockdown increased stemness and IGF1R pathway markers, indicating a shift toward less differentiated states. These findings suggest that SLC2A2 supports liver differentiation by regulating glucose metabolism and suppressing pathways associated with stemness and malignancy. Targeting SLC2A2 may serve as a promising therapeutic strategy for liver-related diseases, particularly HCC, by addressing its dual role in differentiation and tumor progression. Further mechanistic studies are warranted to fully elucidate these processes.